Effect Of Debridement On Mandibula Abscess Patients: Case Study - Kusumawati, Heni (Sean Institute, 2022)
The mandibular abscess is a collection of Pus Pus) in the latent space between the neck cavities caused by aerobic, anaerobic, or mixed bacteria. The most common pathogen found from culture results is streptococcus viridian, staphylococcus epidermidis, staphylococcus aureus, streptococcus hemolytic, fusobacterium bacteria, peptostreptococcus species, Neisseria, klebsiella pneumonia, and pseudo mom. It spreads from various sources of infection, such as teeth, mouth, throat, paranasal sinuses, ears, and neck. This paper aims to provide nursing care for patients who experience postoperative abscess debridement. The research design used is a case study to explore the nursing problems of patients who experience postoperative debridement with acute pain at Adjidarmo Hospital, Lebak-Banten. Data collection through interviews, observation, physical examination, and documentation study. Based on the study's results, it was found that the patient complained of pain in the area of the former operation, pain radiating from the ear to the lower jaw with a pain scale of 7 (0-10) and intermittent. The wound contained Pus. The patient has no appetite, can only finish ½ portion of porridge, has difficulty swallowing, and has difficulty opening his mouth. The results of the leukocyte laboratory examination: 19,900 /µL and the results of the X-ray examination: Mandible (+). Nursing problems that arise are acute pain, infection, anxiety, and the risk of nutritional deficits. The interventions made refer to SIKI and SLKI. The implementation carried out refers to the intervention. The evaluation found nursing problems Mrs. A resolved on the third day with the criteria for decreased pain results with a pain scale of 3 (0-10), no spread of the wound and no pus, and the patient could open his mouth so that his appetite increased. He could finish one portion of food.